The influence of war on civil infrastructures, immigrants, and local residents in Mohsin Hamid's Exit West - Joodaki, Abdoul Hossein; Navidi, Maryam; Dehpahlavan, Talat (Penerbit Universiti Kebangsaan Malaysia, 2024)
The novel, Exit West, by Mohsin Hamid offers a thought-provoking reflection on the impact of infrastructures during times of unavoidable wars and mass immigration. This paper aims to analyse how the novel portrays civil infrastructures and their significance to both immigrants themselves and native residents. As living standards continue to improve, the concept of life infrastructure becomes increasingly diverse and complex. In such circumstances, civil infrastructures play a crucial role in literary works, especially when a city faces significant events. Infrastructures have a profound influence on various literary works that revolve around themes such as inevitable violence and immigration. Therefore, this study takes an in-depth look at the different aspects of civil infrastructures exposed to war.